The Level Of Performance Of Free Player And Relation With Arrange Of Teams Of Aljamhoriaa Championship For Men Of wheelchair Volleyball - Abedulillah, Maher (Journal of Physical Education, 2014)
The importance of research is to analysis effort of free player and his activity according to statistic numbers and rate that coaches make them in training course to achieve win of match. The aims are: 1. Knowing the performance level of defense skills for free player of teams that participate in aljamhoriaa championship for men of wheelchair volleyball . 2. 2-Knowing the relationship between defense skills (reception , defense of playground) for free player with arrange to participated teams in aljamhoriaa championship for men of wheelchair volleyball . The two researchers suppose the teams that have free player are best in arrange than those do not play in this system for wheelchair volleyball. The two researchers show the role of free player and importance of defense skills in wheelchair volleyball games .They use descriptive program analysis style because it suit to a problem ,the sample of research , tools that used ,form of notes , spotting experience and statistic means to output results. The results are: 1. There is relation between level of free player and arrange of teams of championship. 2. There is some teams that do not play in free player system. 3. The best free player is not necessary to be one of win team. 4. Most teams depend on one free player and that makes physical and psychology effort that leads to weakness in success the defense while the new law allow two players. The two researchers recommended to: 1. It is necessary to find more than one free player in team and in training for defense aspects. 2. 2-Be specialization enough time to daily training courses in order to construct defense plans that depend on the major role of free player.